Recent progress in the understanding and treatment of transthyretin amyloidosis. (June 2014) - Sekijima, Y.
Summary What is known and objective Transthyretin (TTR) is a representative amyloidogenic protein in humans. Rate‐limiting tetramer dissociation and rapid monomer misfolding and misassembly of variant TTR result in autosomal dominant familial amyloidosis. Analogous misfolding of wild‐type TTR results in senile systemic amyloidosis (SSA) presenting as sporadic amyloid disease in the elderly. The objective of this review is to summarize recent progress in our understanding and treatment of TTR amyloidosis. Methods Literature searches were conducted on the topics of transthyretin, familial amyloid polyneuropathy and clinical trials, using PubMed, the United States clinical trials directory, pharmaceutical company websites and news reports. The information was collected, evaluated for relevance and quality, critically assessed and summarized. Results and discussion The current standard first‐line treatment of familial TTR amyloidosis is liver transplantation. However, large numbers of patients are not suitable transplant candidates. Recently, the clinical effects of TTR tetramer stabilizers, tafamidis and diflunisal, were demonstrated in randomized clinical trials, and tafamidis has been approved for the treatment of FAP in European countries and Japan. In addition, gene therapies with antisense oligonucleotides and small interfering RNAs are promising strategies to ameliorate TTR amyloidoses and are currently in clinical trials. What is new and conclusions Liver transplantation to treat the familial TTR amyloidosis will likely be replaced by other less invasive therapies, such as TTR tetramer stabilizers and possibly gene therapy approaches. These newly developed therapies are expected to be effective for not only familial TTR amyloidosis but also SSA, based on their mechanisms of action.